O registro como instrumento de reflexão na formação do docente: pesquisa-intervenção em escola municipal de educação infantil - Merli, Angélica de Almeida (2015)
This intervention-research aimed to create collective spaces for reflection in times of continuing education in a public school in kindergarten in the city of São Paulo service. It was studied the registration as a tool for reflection on educational conceptions and practices of childhood education teachers. It started from the hypothesis that, when registering, the teacher moves away from the action itself, which can better reflect on it and this reflection, when shared with the group, enables reorient the educational activity. Thus, the theoretical framework supported the contributions of studies of the Sociology of Childhood (BARBOSA, 2009a, 2009b; FARIA, 2001, 2002; SAMPAIO, 2001) and researchers (MELLO, 1999, 2004, 2009, 2012; HENRIQUES, 2001; ROSSETTI-FERREIRA, 2001; ROSSETTI-FERREIRA; OLIVEIRA 2009) that contribute their research in education based on the historical-cultural theory proposed by Vygostsky. The methodological approach was based on the understanding of the educational process based on the principle of action-reflection-action advocated by Paulo Freire, seeking, in dialogue with participants from practices, questioning them, reflecting and preparing summaries to return them with knowledge (re) constructed. For data collection, the researcher, who is also pedagogical coordinator of the school, developed in the period August to December 2013, the following steps: dialogue with six teachers on planning activities with children; observation of implementing the proposed activities; dialogue with each of the pairs of teachers of the rooms observed and socializing with other teachers in the JEIF´s group (Special Day for Integral Formation), the written records and the reflections systematized after the feedback session with the double. At all stages, the procedures used were written in a field diary recording; registration of the observations made by the coordinator-researcher; recorded audio and transcript of the material; preparing summaries of the dialogues held during feedback moments with the double. As results were found that: there was appreciation of the registration as a tool that contributes to the process of reflection on practice, however, the working conditions and the bureaucratization prevented teachers from registering its actions in order to reflect on them; the socialization of the records made by the teachers and the coordinator-researcher contributed to the process of collective reflection; the use of the registry as a tool that gives visibility to the practice was valued by the educational group; teachers evaluate their practices were valued by the coordinator-researcher and this favored the establishment of trust relationships between teachers and coordination. Thus, the stages of intervention research contributed to the process of action-reflection-action during the moments of in-service training, which had reflecting changes in teaching practices.